BAGAIMANA IMPLEMENTASI KEBIJAKAN PROGRAM BANTUAN PELAKU USAHA MIKRO DI INDONESIA? (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine the implementation of the Micro Business Assistance Program (BPUM) policy in the Department of Trade, Industry, Cooperatives, Small and Medium Enterprises, Bulukumba Regency by referring to the Implementation indicators by George C. Edward, namely Communication, Resources, Disposition (tendencies) , Bureaucratic structure and This type of research uses qualitative methods which aim to provide an overview of the implementation of the Micro Business Assistance Program (BPUM) policy in Trade, Industry, Cooperatives, Small and Medium Enterprises, Bulukumba Regency. Data sources consist of primary data obtained through interviews, and secondary data taken from documents, notes, reports and official archives which can be supported by the integrity of the primary data.